Among Weaknesses, Sensibilities and Vulnerabilities: The West’s Cognitive Sources of the Self (Economic and Political Thought, 2024)
The article’s purpose is to identify and describe briefly the pronounced features of the Western thinking stemming from the philosophical, religious and political traditions which run a different course in comparision with the Eastern patterns (Middle Eastern and Asian). The thesis proposed is that the differences are irreconciable but managable. The article’s thesis is that the current escalation of tensions in the world accompanied by the uptick of enthusiasm for authoritarian forms of governance are a transitionary pheonemenon stemming from the intelectual crisis in the West, institutional inadequacies, the enrichment of new social classes and the replacement of old elites with new ones.The text is otlining the weakneses of the West symbolized by Hamlet’s syndrom as well as abstract modern paradigms of analysis proposed by various philosophical schools which undermined the existing orders not offering much.
Keywords: Western democratic tradition, Western overintellectualism as the source of weakness, “Kanthian revolution” in thinking, authoritarian tendencies, sources of Chinese conduct